2011
DOI: 10.1016/j.ajpath.2011.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Contributes to Podocyte Injury by Increasing TRPC6 Expression via an NFAT-Mediated Positive Feedback Signaling Pathway

Abstract: The transient receptor potential channel C6 (TRPC6) is a slit diaphragm-associated protein in podocytes involved in regulating glomerular filter function. Gain-of-function mutations in TRPC6 cause hereditary focal segmental glomerulosclerosis (FSGS), and several human acquired proteinuric diseases show increased glomerular TRPC6 expression. Angiotensin II (AngII) is a key contributor to glomerular disease and may regulate TRPC6 expression in nonrenal cells. We demonstrate that AngII regulates TRPC6 mRNA and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
219
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(230 citation statements)
references
References 58 publications
10
219
1
Order By: Relevance
“…Such a loop could potentially parallel or augment the well established positive feedback loop involving the TRPC6-calcineurin-NFAT pathway (25,26,103), especially because ERK activation in our system was inhibited by cyclosporine A.…”
Section: Discussionmentioning
confidence: 99%
“…Such a loop could potentially parallel or augment the well established positive feedback loop involving the TRPC6-calcineurin-NFAT pathway (25,26,103), especially because ERK activation in our system was inhibited by cyclosporine A.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, calcineurin inhibition by cyclosporine decreased TRPC6 expression and reduced proteinuria, whereas podocyte-specific inducible expression of a constitutively active NFAT mutant increased TRPC6 expression and induced severe proteinuria. These important findings demonstrated that the deleterious effects of Ang II on podocytes and its pathogenic role in glomerular diseases most probably involve an enhanced TRPC6 expression via a calcineurin/NFAT positive feedback signaling pathway (51).…”
Section: Interaction Of Trpc6 With Other Sd Proteins Of the Filtratiomentioning
confidence: 91%
“…Moreover, TRPC6 expression correlated with glomerular damage markers and glomerulosclerosis. The regulation of TRPC6 expression by Ang II required TRPC6-mediated Ca 2+ influx and the activation of calcineurin and its substrate NFAT (51). Accordingly, calcineurin inhibition by cyclosporine decreased TRPC6 expression and reduced proteinuria, whereas podocyte-specific inducible expression of a constitutively active NFAT mutant increased TRPC6 expression and induced severe proteinuria.…”
Section: Interaction Of Trpc6 With Other Sd Proteins Of the Filtratiomentioning
confidence: 99%
See 2 more Smart Citations